1994
DOI: 10.1051/gse:19940202
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of mixed linear models via Gibbs sampling with an application to litter size in Iberian pigs

Abstract: The Gibbs sampling is a Monte-Carlo procedure for generating random samples from joint distributions through sampling from and updating conditional distributions. Inferences about unknown parameters are made by: 1) computing directly summary statistics from the samples; or 2) estimating the marginal density of an unknown, and then obtaining summary statistics from the density. All conditional distributions needed to implement the Gibbs sampling in a univariate Gaussian mixed linear model are presented in scala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 20 publications
0
110
0
4
Order By: Relevance
“…In each of the mapping procedures, permutation test was exploited to control genome-wide false positive rate. Parameters of the full-QTL model were estimated using a Bayesian method via Gibbs sampling (Wang et al 1994). A relative contribution was calculated as the proportion of variance caused by a specific genetic source in the total phenotypic variance, and the general contribution for each genetic source was calculated from the relative contributions of all the putative QTL involved.…”
Section: Discussionmentioning
confidence: 99%
“…In each of the mapping procedures, permutation test was exploited to control genome-wide false positive rate. Parameters of the full-QTL model were estimated using a Bayesian method via Gibbs sampling (Wang et al 1994). A relative contribution was calculated as the proportion of variance caused by a specific genetic source in the total phenotypic variance, and the general contribution for each genetic source was calculated from the relative contributions of all the putative QTL involved.…”
Section: Discussionmentioning
confidence: 99%
“…An F test was executed at all stepwise model selection procedures. The Bayesian method using Gibbs sampling (Wang 1994) as a type of Markov Chain Monte Carlo (MCMC) was used to estimate parameters in the model without the consideration for the distribution of canopy wilting. For each sequential model in one-and two-genome scans, a permutation test (1000 times) (Churchill and Doerge 1994) was applied for new coefficient terms in the model (Yang et al 2007) to determine the empirical experiment-wise false-positive rate.…”
Section: Qtl Analysis and Mappingmentioning
confidence: 99%
“…Using well known results (e.g., Wang et al 1993Wang et al , 1994Sorensen and Gianola 2002) it can be shown that…”
Section: Conditional Posterior Distribution Of Genomic Effectsmentioning
confidence: 96%
“…As shown by Wang et al (1993Wang et al ( , 1994) the conditional posterior distribution of b given everything else is the multivariate normal process…”
Section: Conditional Posterior Distributions Of Other Location and DImentioning
confidence: 98%